2013
DOI: 10.3126/nepjoph.v5i2.8733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of xerophthalmia in rural children of Uttarpradesh, India

Abstract: The presence of a milder manifestation of xerophthalmia and a 0.9 % prevalence of Bitot's spot in children under six years of age in the present study shows a declining trend of VAD although it is still a public health problem. The higher prevalence in children above six years of age shows that apart from strengthening of Vitamin A prophylaxis programs, health education is needed for dietary diversification to include vegetables and fruits in the diet for long-term sustainability in improving the vitamin A sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The working definition, study period, and the tool were almost similar that gives a consistent result [48]. But, the magnitude of xerophthalmia in this study is higher than reports in Asgede Tsimbla rural district of Northern Ethiopia [38], Jimma town, Ethiopia [36], Southern Ethiopia [33], northern Sudan [17], traditional Quran bordering school of Sudan [49], Nigeria [28], Malawi [29], Cameron [30], Southeast Asia [50], Nepal [22], Philippines [23], northern Bangladesh [24], west java, Indonesia [25], Thailand [26], Cambodia [27], Yemen [51] and Ahmadabad, India [20]. This discrepancy might be due to the sociocultural variation among the study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The working definition, study period, and the tool were almost similar that gives a consistent result [48]. But, the magnitude of xerophthalmia in this study is higher than reports in Asgede Tsimbla rural district of Northern Ethiopia [38], Jimma town, Ethiopia [36], Southern Ethiopia [33], northern Sudan [17], traditional Quran bordering school of Sudan [49], Nigeria [28], Malawi [29], Cameron [30], Southeast Asia [50], Nepal [22], Philippines [23], northern Bangladesh [24], west java, Indonesia [25], Thailand [26], Cambodia [27], Yemen [51] and Ahmadabad, India [20]. This discrepancy might be due to the sociocultural variation among the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Researches done across different Asian countries showed that the prevalence of xerophthalmia ranges from 0.48% to 22.3% in different target populations [2027].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of micronutrient deficiencies and associated factors was studied among South Asian adolescents. Association between the prevalence of vitamin A deficiency and sex was not significant in two publications (76,87) ; however, another publication found that xerophthalmia as defined by Bitot spots and/or night blindness was significantly associated with adolescent boys (88) . While iron deficiency (74) and vitamin D deficiency (82,83) were significantly higher among females, vitamin B12 deficiency was significantly more common among males (89) .…”
Section: 24mentioning
confidence: 90%
“…They require a high supply of nutrients since they are usually very active and their growth rate is rapid. Moreover, during this period, nutritional diseases in the form of kwashiorkor, marasmus, anaemia, and xerophthalmia are not uncommon [32][33][34]. Preschool children call for focused attention in India as because the country has the world's highest percentage of undernourished children [35].…”
Section: Introductionmentioning
confidence: 99%